P308 A review of the impact of shift-work on occupational cancer. (1st September 2016) - McElvenny, Damien; Crawford, Joanne; Davis, Alice; Dixon, Ken; Alexander, Carla; Cowie, Hilary; Cherrie, John
Abstract : The International Agency for Research on Cancer has classified shift-work involving circadian disruption as probably carcinogenic in humans, with evidence strongest for long-term female night workers and breast cancer. It regarded the epidemiological data as being limited by possible confounding and inconsistent definitions of shift-work. Epidemiological reviews and studies reporting mechanistic data and health and safety policies and practices since 2005 were identified and selected for review according to specific inclusion/exclusion criteria. Individual cohort and case-control studies studies since 2013 were also included. The relative risk of breast cancer for ever versus never working nights is lower in recent epidemiological studies than when the association first came to our attention 15 years ago, probably due to better control for confounding. There are also increasingly well conducted studies that look at a range of measures associated with chronodisruption and which also account for a large number of known and potential confounding factors. Some of these studies provide evidence of an increasing risk with increased duration of working nights. However, the heterogeneity in exposure-response means that a casual determination remains elusive. We conclude that the most likely causal mechanism for a breast cancer risk amongst night shift workers is suppression of melatonin because of exposure to light at night, although the risk may be modified by other circadian factors such as chronotype. However, it is also plausible that there may be direct or indirect causal pathways because of the tendency for shift workers to be obese, and have other lifestyle risk factors for breast cancer. Aside from the possible indirect benefit of formulating shift patterns that maximise workers' alertness, we believe the most useful intervention is in health promotion, in which employers actively provide healthy diets, opportunities to exercise, and discourage tobacco smoking and alcohol consumption.